Lensless Tomographic Imaging of Near Surface Structures of Frozen Hydrated Malaria-Infected Human Erythrocytes by Coherent X-Ray Diffraction Microscopy. Issue 1 (December 2017) - Frank, Viktoria; Chushkin, Yuriy; Fröhlich, Benjamin; Abuillan, Wasim; Rieger, Harden; Becker, Alexandra; Yamamoto, Akihisa; Rossetti, Fernanda; Kaufmann, Stefan; Lanzer, Michael; Zontone, Federico; Tanaka, Motomu
Abstract Lensless, coherent X-ray diffraction microscopy has been drawing considerable attentions for tomographic imaging of whole human cells. In this study, we performed cryogenic coherent X-ray diffraction imaging of human erythrocytes with and without malaria infection. To shed light on structural features near the surface, "ghost cells" were prepared by the removal of cytoplasm. From two-dimensional images, we found that the surface of erythrocytes after 32 h of infection became much rougher compared to that of healthy, uninfected erythrocytes. The Gaussian roughness of an infected erythrocyte surface (69 nm) is about two times larger than that of an uninfected one (31 nm), reflecting the formation of protein knobs on infected erythrocyte surfaces. Three-dimensional tomography further enables to obtain images of the whole cells with no remarkable radiation damage, whose accuracy was estimated using phase retrieval transfer functions to be as good as 64 nm for uninfected and 80 nm for infected erythrocytes, respectively. Future improvements in phase retrieval algorithm, increase in degree of coherence, and higher flux in combination with complementary X-ray fluorescence are necessary to gain both structural and chemical details of mesoscopic architectures, such as cytoskeletons, membraneous structures, and protein complexes, in frozen hydrated human cells, especially under diseased states.